The Christchurch Mosque Massacre: Terror and Hope - Pratt, Douglas (Journal for the academic study of religion, 2020)
On 15 March 2019 New Zealand was subject to a violent terrorist act seemingly born of a number of threads of extremism. A white supremacist, motivated by a mix of race hatred, anti-immigration sentiment and palpable hostility toward Muslims, callously executed over 50 persons at two mosques in the city of Christchurch, New Zealand, injuring many others. What motivated this attack? What lies behind it? What has emerged in the aftermath? It is tempting to simplify, to pin the underlying cause on one element, such as racism. This article analyses and discusses the mosque massacre and its driving ideology in light of five ‘lenses’, or threads, of terrorism. Religion, the fifth of these, was a critical component of the choice of target and arguably integral to the complex ideology that, at least in part, inspired and motivated the attacker. Responses to the event, including signs of hope evident in its aftermath, will also be discussed.